Distribution of Mutans Streptococci in Orthodontic Patients: Pilot Study - Emad Husseın; Alev Aksoy-Doğan (Galenos Yayinevi, 2009)
The aim of the present study is to monitor Mutans Streptococcus (MS) level and sites of teeth using a novel imprint technique, before and after bonding orthodontic brackets. The study included 30 orthodontic patients. An imprint was obtained by pressing a solid sucrose-containing matrix against the sampled tooth surfaces. Following incubation, the matrix was examined directly for bacterial outgrowth. A significant increase in MS levels were found after bonding a fixed orthodontic appliance (p<.05). The right and left canines were the teeth scored the highest increase in the mean reading for accumulation of MS. The gingival third of the teeth, and the area around the brackets were the most preferable sites for bacterial outgrowth, while the incisal areas of the centrals and laterals were the least favorable site for bacterial outgrowth. The results of this study can help in screening and classifying the high-risk individuals among orthodontic patients. Special concern must be given to the high- risk patients, the high-risk teeth and the most favorable sites for bacterial accumulation. These teeth and sites should be treated more carefully and pursued under a more frequent regimen of caries control before and during orthodontic treatment.